Pengaruh Media Komik Tematik Terhadap Hasil Belajar Kognitif - Wacana Akademika; Aan Feriansyah (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2021)
Thematic comics are one of the interesting learning media for students. This study aims to determine the effect of thematic comic media on cognitive value learning outcomes. The research was conducted in one of the public elementary schools in Palembang. This research is a quantitative-research with a true-experimental design type, posttest-only control design. The sampling technique used is saturated sampling with the type of probability sampling. The samples used were class II A and class II B. This study used an experimental method with data collection techniques used in this study were interviews, documentation and tests. Data were analyzed using data normality test, homogeneity test, validity test, reliability test and independent sample t-test. The results showed that there was an influence on the cognitive value of students after using thematic comic media, this was indicated by the significant influence of cognitive values ​​on second grade students in one of the public elementary schools in Palembang.